The effect of accruals quality (Dechow & Dichev Model) on performance of manufacturing companies listed in Indonesia Stock Exchange period 2004 - 2010 - Megawati Yulfitri Ayu; Nurmala Ahmar (The Indonesian Accounting Review, 2013)
The objective of this study is to examine the effect of accruals quality toward companyperformance for manufacturing companies in Indonesian Stock Exchange 2004-2010.The company's performance as the dependent variable in this study is measured usingtwo indicators of the performance of the company's operations (ROAt+1) and marketperformance of companies (Tobins Q) and uses the size and leverage as a controlvariable. This study uses a purposive sampling method that retrieves all manufacturingcompanies in Indonesia Stock Exchange and with the result of 102 manufacturingcompany as a sample. The test the normality of data is done using the test Kolmogorof-Smirnov with the program spss 17 version for windows. The analysis hypothesis isusing linear regression. The result of this study showed that accruals quality affectsthe company's performance if it is measured using indicators ROAt+1, but the accrualsquality does not affect the company's performance if measured using indicatorsTobins Q.